2018
DOI: 10.1038/s41598-018-32783-7
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive nanosecond electroporation for biocontrol of surface infections: an in vivo study

Abstract: Invasive infections caused by drug-resistant bacteria are frequently responsible for fatal sepsis, morbidity and mortality rates. In this work, we propose a new methodology based on nanosecond high frequency electric field bursts, which enables successful eradication of bacteria in vivo. High frequency (15 kHz) 15–25 kV/cm 300–900 ns pulsing bursts were used separately and in combination with acetic acid (0.1–1%) to treat Pseudomonas aeruginosa in a murine model. Acetic acid 1% alone was effective resulting in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 59 publications
0
10
1
Order By: Relevance
“…The energy levels necessary for the electroporation-supported therapy are similar to the intensities used for ECT in vivo [44]. For the successive clinical electrochemotherapy of human breast cancer with bleomycin, Whelan et al applied pulses of intensity 1400 V/cm, 100 µs duration [45].…”
Section: Discussionmentioning
confidence: 99%
“…The energy levels necessary for the electroporation-supported therapy are similar to the intensities used for ECT in vivo [44]. For the successive clinical electrochemotherapy of human breast cancer with bleomycin, Whelan et al applied pulses of intensity 1400 V/cm, 100 µs duration [45].…”
Section: Discussionmentioning
confidence: 99%
“…As indicated in Table 3.1, the device was successfully used to investigate the nsPEF effects, which resulted the proposal of new treatment methodologies and non-viral gene delivery methods proof of concept (Novickij, Rembialkowska, et al 2020;Ruzgys et al 2018;Novickij, Zinkevičienė, Perminaitė, et al 2018;Novickij, Stanevičienė, et al 2020;Novickij, Zinkevičienė, Valiulis, et al 2018;Novickij, Zinkevičienė, Stanevičienė, et al 2018;Novickij, Česna, et al 2019), which confirmed, that nsPEF bursts can be used for eradication of bacteria. The developed square-wave systems application has also included the research in MHz pulse repetition frequency range (Ruzgys et al 2019;Pakhomov et al 2019).…”
Section: The Application Of Prototype System For Electroporationmentioning
confidence: 84%
“…We believe, that the potential solution to the mentioned problems is to use the topical delivery of acetic acid to serve as a high impedance electrode/tissue interface and deliver the pulses using electrodes without forming a skin lump or keeping it minimal. The difference in load bioimpedances would result in only a thin layer of epidermis being affected, while the depth of ablation could be controlled by the bioimpedance of the electrode/tissue contact and by the amplitude of electric field [65]. In cases of wound treatment, the low penetration depth of PEF is advantageous, since it will allow to sustain the PEF effect predominantly in the infected volume.…”
Section: Discussionmentioning
confidence: 99%